The management of the COVID-19 health crisis in Algeria: Measures and methods - Kaddour, Brahim Hadj; Abderrahmane, Djoher (The International tax journal, 2025)
The COVID-19 health crisis posed major challenges for Algeria, particularly in the healthcare and economic sectors. The government adopted several measures, including lockdowns, border closures, and intensified awareness campaigns to curb the spread of the virus. Field hospitals were set up, and medical equipment was supplied to respond to the surge in infections. However, the crisis revealed significant weaknesses in the healthcare infrastructure, as well as shortages in human resources and essential equipment. Despite these challenges, the crisis highlighted the urgent need to improve the healthcare system and to strengthen preparedness for future emergencies.